Application of Problem Based Learning Model Assisted by Augmented Reality Media to Improve Students’ High Order Thinking Skills - Erin Lespita; Andik Purwanto; Ahmad Syarkowi (Jurnal Pendidikan Fisika, 2023)
This study aims to determine the increase in the level of students’ High Order Thinking Skills (HOTs) after being given learning with a Problem Based Learning (PBL) model assisted by Augmented Reality (AR) media. This study was a quantitative research using Pre-Experimental method in the form of one group pretest-posttest design. The sample of this study was 31 students of class X IPA SMA Negeri 9 Bengkulu City. The research data was collected through 3 stages, namely the pretest, treatment using the Problem Based Learning model assisted by Augmented Reality media, and the post-test. The research data was processed with the help of statistical software package for social sciences (SPSS) 20. Data analysis was carried out through Statistical Descriptive Test, then Data Normality Test with Klomogorov Smirnov. The results of data analysis showed that the data sample was normally distributed with a significance value of 0.29, that is more than 0.05, and further data analysis used the Parametric Paired Pample T-test. Based on the data analysis, it was concluded that Ha was accepted with a sig. 2 tailed 0.00 is less than 0.05. Therefore, it can be concluded that there is an increase in the level of students’ High Order Thinking Skills after the implementation of the problem-based learning model assisted by augmented reality media with an N-gain value of 0.36 in the category of medium level of improvement.